PENGEMBANGAN INSTRUMEN PENILAIAN PEMBELAJARAN BAHASA ARAB - Rahmadon Rahmadon; Mikyal Oktarina (Jurnal Pendidikan Nusantara, 2025)
Assessment is an important component in the Arabic language learning process because it serves to comprehensively measure the achievement of student competence. However, the assessment instruments used in schools often do not meet the principles of validity, reliability, and practicality, especially in assessing Arabic language skills, which include maharah istima’, kalam, qira’ah, and kitabah. This study aims to develop a valid, reliable, and practical Arabic language learning assessment instrument. The research method used is research and development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The instruments developed include written tests, oral tests, and performance assessment rubrics. Expert validation results show that the instrument is highly valid, while limited trials show a high level of reliability and ease of use by teachers. Thus, the assessment instrument developed is suitable for use in improving the quality of Arabic language learning evaluation